Spleen nodules in Loa loa infection: re-emerging knowledge and future perspectives. Issue 7 (July 2022) - Tamarozzi, Francesca; Buonfrate, Dora; Ricaboni, Davide; Ursini, Tamara; Foti, Giovanni; Gobbi, Federico
Summary: Loiasis, the infection with the vector-borne filarial nematode Loa loa, is widely distributed in central and west Africa. Long considered a rather benign infection, recently loiasis with high microfilarial burden was associated with increased mortality risk. Eyeworm and Calabar swelling are pathognomonic signs of the infection, but other atypical, non-specific manifestations can also occur. For instance, splenic nodules have been seldom reported. In this Grand Round, we report two cases of loiasis in migrants who presented with spleen nodules, which could be followed up over time (up to 27 months) with multiple imaging techniques until their resolution. We comment on the clinical implications of these observations, including differential diagnosis with similar imaging findings, and critically review the evidence of spleen involvement in loiasis and other filarial infections.